Dukungan Keluarga Remaja Karang Taruna dalam Mencegah Timbulnya Penyakit dan Merokok melalui Keperawatan Komunitas Desa Kalibeji Sempor Kebumen - Marsito; Rina Saraswati; Kholifatun Nurrohwinahyu (HEALTH CARE : JURNAL KESEHATAN, 2022)
Based on the Central Statistics Agency, adolescents aged 15 to 19 years in Indonesia experienced an increase in smoking frequency and the percentage of smokers aged 15-19 years had increased in 2020. There were 10.61% of the population aged 15-19 years who smoked in 2020, up from 10 .54% in 2019. Meanwhile, the smoking rate for adolescents from 15 to 19 years old is 9.98% (BPS, 2021). Looking at the data and the increase in adolescent smoking, the researchers used community nursing concept questions (CAP). Such as family support, adolescent smoking, the incidence of illness can be data using CAP. The purpose of this study was to look at the family support of youth youth groups, youth smoking, adolescents who were sick, and linking family support to smoking and the incidence of illness. This study links adolescent family support with smoking and disease. The methodology is an exploratory description with the population of teenagers in Kalibeji village and the total number of samples is 441 people. Researchers gave consent before taking data, and they agreed. From the results of the study, it was found that the family support of teenagers was very supportive of 285 people (60.1%), 402 people who did not smoke (91.2%), healthy teenagers there were 430 people (97.5%). For the relationship between adolescent family support and smoking there is a relationship = 0.0003 while adolescent family support with the incidence of illness has no relationship = 0.082. It is recommended that families remind teenagers not to smoke and take care of their health. And the Betty Neuman model with community as partner in community nursing can be used to study adolescents.